Effects of endovascular cooling on infarct size in ST‐segment elevation myocardial infarction: A patient‐level pooled analysis from randomized trials. (14th December 2017) - Dae, Michael; O'Neill, William; Grines, Cindy; Dixon, Simon; Erlinge, David; Noc, Marko; Holzer, Michael; Dee, Anne
Abstract : Objectives: This study sought to examine the relationship between temperature at reperfusion and infarct size. Background: Hypothermia consistently reduces infarct size when administered prior to reperfusion in animal studies, however, clinical results have been inconsistent. Methods: We performed a patient‐level pooled analysis from six randomized control trials of endovascular cooling during primary percutaneous coronary intervention (PCI) for ST‐segment elevation myocardial infarction (STEMI) in 629 patients in which infarct size was assessed within 1 month after randomization by either single‐photon emission computed tomography (SPECT) or cardiac magnetic resonance imaging (cMR). Results: In anterior infarct patients, after controlling for variability between studies, mean infarct size in controls was 21.3 (95%CI 17.4‐25.3) and in patients with hypothermia <35°C it was 14.8 (95%CI 10.1‐19.6), which was a statistically significant absolute reduction of 6.5%, or a 30% relative reduction in infarct size ( P = 0.03). There was no significant difference in infarct size in anterior ≥35°C, or inferior infarct patients. There was no difference in the incidence of death, ventricular arrhythmias, or re‐infarction due to stent thrombosis between hypothermia and control patients. Conclusions: The present study, drawn from a patient‐level pooled analysis of six randomized trials of endovascular cooling during primary PCI in STEMI, showed a significant reduction in infarct size in patients with anterior STEMI who were cooled to <35°C at the time of reperfusion. The results support the need for trials in patients with anterior STEMI using more powerful cooling devices to optimize the delivery of hypothermia prior to reperfusion.